2007
DOI: 10.1093/cercor/bhm073
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Gamma-Band Phase Synchronization and Selective Attention

Abstract: Explaining the emergence of a coherent conscious percept and an intentional agent from the activity of distributed neurons is key to understanding how the brain produces higher cognitive processes. Gamma-band synchronization has been proposed to be a mechanism for the functional integration of neural populations that together form a transitory, large-scale, task- and/or percept-specific network. The operation of this mechanism in the context of attention orienting entails that cortical regions representing att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
140
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(163 citation statements)
references
References 49 publications
13
140
0
3
Order By: Relevance
“…This result is supported by three sources of evidence: (i) tau expression is densely expressed in frontal regions (see Fig. 1C) as previously reported (Goerdert et al, 1989;Trojanowski et al, 1989;Santa-Maria et al, 2005;McMillan et al, 2008), (ii) anatomical studies have demonstrated the existence of a monosynaptic pathway from the hippocampus to the frontal cortex (Swanson, 1981;Ferino et al, 1987;Thierry et al, 2000), and (iii) gamma-band synchronization between distant brain regions, including the frontal lobe, has been involved in a variety of cognitive processes, such as perception, attentional selection, and memory (Desmedt and Tomberg, 1994;Von stein et al, 2000;Doesburg et al, 2008Doesburg et al, , 2009Sehatpour et al, 2008). Combining more specific cognitive tests with long-range gamma synchronization measurements could be a more adequate approach at providing novel insights into the role of tau in cognitive functions.…”
Section: Discussionsupporting
confidence: 78%
“…This result is supported by three sources of evidence: (i) tau expression is densely expressed in frontal regions (see Fig. 1C) as previously reported (Goerdert et al, 1989;Trojanowski et al, 1989;Santa-Maria et al, 2005;McMillan et al, 2008), (ii) anatomical studies have demonstrated the existence of a monosynaptic pathway from the hippocampus to the frontal cortex (Swanson, 1981;Ferino et al, 1987;Thierry et al, 2000), and (iii) gamma-band synchronization between distant brain regions, including the frontal lobe, has been involved in a variety of cognitive processes, such as perception, attentional selection, and memory (Desmedt and Tomberg, 1994;Von stein et al, 2000;Doesburg et al, 2008Doesburg et al, , 2009Sehatpour et al, 2008). Combining more specific cognitive tests with long-range gamma synchronization measurements could be a more adequate approach at providing novel insights into the role of tau in cognitive functions.…”
Section: Discussionsupporting
confidence: 78%
“…The key idea is that stimulus selection is achieved by establishing stable phase relationships of spiking activity among selected populations of neurons, enabling thereby effective communication across processing levels (Fries, 2005;Womelsdorf et al, 2007). In support of his hypothesis, there is now abundant evidence showing that gamma oscillations are modulated by attention both in monkeys Bichot et al, 2005;Taylor et al, 2005;Rotermund et al, 2009) and humans (Fell et al, 2002;Doesburg et al, 2008;Garcia-Garcia et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…These works were followed by efforts to develop better computational methods (see Gevins, 1988Gevins, , 1989Gevins et al, 1990;Perrin et al, 1989;Law et al, 1993a;Yao, 2002;Carvalhaes and Suppes, 2011) as well as attempts to combine the surface Laplacian with other methods (Kayser and Tenke, 2006b,a;Carvalhaes et al, 2009), making the technique increasingly popular among EEG researchers. For instance, modern applications include studies on generators of event-related potentials (Kayser and Tenke, 2006b,a), quantitative EEG (Tenke et al, 2011), spectral coherence , event-related synchronization/desynchronization (Del Percio et al, 2007), phase-lock synchronization (Doesburg et al, 2008), estimation of cortical connectivity (Astolfi et al, 2007), high-frequency EEG Fitzgibbon et al (2013), and brain-computer interface (Lu et al, 2013), just to mention a few.…”
Section: Introductionmentioning
confidence: 99%